Spatio‐Temporal Domains of Wildfire‐Prone Teleconnection Patterns in the Western Mediterranean Basin. Issue 19 (6th October 2021) - Rodrigues, Marcos; Mariani, Michela; Russo, Ana; Salis, Michele; Galizia, Luiz Felipe; Cardil, Adrian
Abstract: This work explores the main climate teleconnections influencing the Western Mediterranean Basin to outline homogeneous fire‐prone weather domains combining cross‐correlation time series and cluster analysis. We found a zonal effect of the Scandinavian pattern over the entire region with an interesting alternation of phases from positive during winter‐spring (increased rainfall leading to fuel accumulation) to negative (dry conditions) modes during summer controlling burned area and fire size. The North Atlantic Oscillation (NAO) dominates the number of fires over the Iberian Peninsula (IP) while the Western Mediterranean Oscillation pattern modulates fire activity over the Mediterranean coast in the IP (linked to westerly winds), Southern France, Corsica and Sardinia (rainfall regulation). These distinctive influence traits resulted in three different domains splitting the IP into a Mediterranean rim along the coast (from southern Spain to southwestern France) and an inland and western region (Portugal plus western Spain); and a third in southeastern France, Corsica and Sardinia. Plain Language Summary: We synthetized the climate influence on wildfire activity over the Western Mediterranean Basin into three distinctive configurations. We applied computer‐assisted statistical analysis on historical fire records from national/regional agencies and climate‐related data [the so‐called climate teleconnection indexes; e.g., "El Niño" or the North Atlantic Oscillation (NAO)]. Burned area size over the entire basin tends to be larger under the confluence of rainy winter‐spring and sudden heat waves and dry spells during summer, which is governed by the Scandinavian pattern. In the Mediterranean coast of Spain fires occur more frequently under sustained calm and warm conditions while they grow larger when winds blow from the western side of the Iberian Peninsula. These conditions depend on the NAO and Western Mediterranean Oscillation (WeMOi) pattern, respectively. Fire activity in Southern France, Corsica and Sardinia seems to be linked to the lack of rainfall, which is regulated by the atmospheric conditions over the Mediterranean sea, mostly controlled by the WeMOi pattern. Key Points: We found three distinctive but homogenous domains of influence of climate teleconnections patterns The Scandinavian pattern exerts a zonal influence over the western Mediterranean basin. North Atlantic Oscillation controls the Iberian Peninsula and Western Mediterranean Oscillation the Mediterranean coast Positive moisture winter‐spring anomalies coupled to short‐term dry and warm conditions boost most of the wildfire activity